Penerapan Sistem Informasi Persuratan Dengan Legalisasi Digital Signature Di Universitas Pendidikan Indonesia - Aswari Aswari; Feri Sulianta (Ridwan Institute, 2022)
Correspondence is a routine work within an organization. Indonesia University of Education, a university located in Bandung, also carries out correspondence activities to support the administrative process. Indonesia University of Education issued the letters manually so far so the distribution takes time. Moreover, in drafting process, the form and format of the letters are often not uniform. Therefore, this information system was established to manage the correspondence process by using digital signatures certified by the Electronic Certification Center (BSrE)-National Cyber and Crypto Agency (BSSN) to secure electronic documents. In addition, the system will help to manage outgoing letters, incoming letters, and dispositions. This system is expected to assist in the issuance of electronic letters and can simplify the bureaucratic procedures within the Indonesia University of Education.